The Influence of Product Quality and Price Perception on the Purchase Decision of Wardah Pressed Powder in Surabaya - Ruth Agita Purba; Hery Pudjoprastyono (Universitas KH. Abdul Chalim Mojokerto, 2025)
As public attention to appearance increases, especially among women, the use of cosmetics has become an important part of daily grooming. The rapid development of cosmetic trends has led to the emergence of various brands, both local and international, resulting in increasingly intense market competition. This study aims to analyze the impact of Product Quality and Price Perception on the Purchase Decision of Wardah pressed powder in Surabaya. This research uses a quantitative approach with purposive sampling method and involves 96 respondents residing in Surabaya. The data were collected through a questionnaire distributed via Google Form and analyzed using SmartPLS 3. The results of the analysis using the Partial Least Square (PLS) method indicate that Product Quality and Price Perception have a positive and significant effect on Purchase Decisions.